Synthesis of Some Trisazo Pyrazolone Acid Dyes and Their Application on Wool and Nylon - Bhavsar, R.A.; Desai, C.M. (Asian Journal of Chemistry, 2010)
Monoazo pyrazolone dyes are very common but trisazo pyrazolone dyeswith arylazo group in position-4 and second arylazo group at position-4of phenyl nucleus and third arylazo group at position-7 of naphthyl nucleusof H or γ acid are not available. Firstly aryldiazonium chloride is coupledin alkaline medium with 1-phenyl-3-methyl-5-pyrazolone or 1(2'chlorophenyl)-3-methyl-5-pyrazolone and the second arylazo group inposition 4' of 1-phenyl group in acidic medium and the third arylazo groupin position 7' of 4-napthyl group of H or γ acid in alkaline medium.